TNF SUPERFAMILY NETWORKS: Bidirectional and Interference Pathways of the Herpesvirus Entry Mediator (TNFSF14) - Ware, Carl F. (2011)
The herpesvirus entry mediator (HVEM; TNFRSF14) can activate either proinflammatory or inhibitory signaling pathways. HVEM engages two distinct types of ligands, the canonical TNF-related cytokines, LIGHT and Lymphotoxin-α, and the Ig-related membrane proteins, BTLA (B and T lymphocyte attenuator) and CD160. Recent evidence indicates that the signal generated by HVEM depends on the context of its ligands expressed in trans or in cis. HVEM engagement by all of its ligands in trans initiates bidirectional signaling. In contrast, naïve T cells coexpress BTLA and HVEM forming a cis-complex that interferes with the activation of HVEM by extraneous ligands in the surrounding microenvironment. The HVEM network is emerging as a key survival system for effector and memory T cells in mucosal tissues.